Using GPS collars to determine parturition and cause‐specific mortality of moose calves - William J. Severud; Glenn Del Giudice; Tyler R. Obermoller; Thomas A. Enright; Robert G. Wright; James D. Forester (Wildlife Society Bulletin)
ABSTRACT Global positioning system (GPS) collars have been deployed on adult moose (Alces americanus) and other ungulates to study various aspects of their ecology, but until the current study they have not been fitted to moose neonates. The moose population in northeastern Minnesota, USA, has been declining since 2006, and information on neonatal survival and cause‐specific mortality are needed. We monitored hourly movements of GPS‐collared females for indications of calving. During 2 May–2 June 2013 we observed 47 of 73 collared females (50 known pregnant, 17 not pregnant, 6 unknown pregnancy status) make “calving movements” followed by a clustering of locations. After allowing a mean bonding time of 40.2 hr, we approached their calving sites and captured and GPS‐collared 49 neonates from 31 dams. We closely monitored dam–calf movements and launched rapid investigative responses to calf mortality notifications to determine cause of mortality. Mean response time was 53.3 hr, but ranged from 0.3 hr to 579 hr, depending on collar accessibility and proper functioning of the GPS component. We censored capture‐related mortalities and slipped collars. Twenty‐five of 34 calves (74%) died of natural causes as of 31 December 2013, including 1 after natural abandonment, 1 after abandonment of unknown cause, 1 drowning, 1 unknown predator kill, 1 lethal infection from wolf (Canis lupus) bites, 4 black bear (Ursus americanus) kills, 12 wolf kills, and 4 “probable wolf kills.” As this technology develops, the quantity and quality of survival, cause‐specific mortality, movement, and habitat use data generated from intense monitoring of GPS‐collared adults and offspring will have unprecedented value associated with management at the population and landscape scales. © 2015 The Wildlife Society.